2017
DOI: 10.1021/acsomega.7b01141
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-Driven Sensor Fabrication of Polydiacetylene-on-Silica Plate in 30 Seconds: Facile Utilization of π-Monomers with C18- to C25-Long Alkyl Chain

Abstract: By utilizing the capillary-force-driven action, a novel polydiacetylene-based sensor on the porous silica plate was developed within 30 s for π-diacetylene monomers with variable chain lengths. This method enables one to utilize diacetylene monomers even with the shorter alkyl chain length of C18–C21, which has not been possible with conventional methods. The invented sensor platform employing shorter monomers was found to perform better, as was demonstrated for gaseous and aqueous analytes, i.e., ammonia gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The color visualization character of PDAs and particularly their distinct color transition induced upon external stimuli have made them a possible choice for colorimetric sensing applications. Because the chromogenic PDAs for TeDA, TrDA, and DiDA can be readily prepared by UV irradiation, subsequently, the colorimetric response toward heat and the organic solvent was investigated. We first began studying thermochromism of polymeric PDAs in the solid phase by heating gradually from 30 to 220 °C on a hot plate, which led to a naked-eye detectable periodic color change as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The color visualization character of PDAs and particularly their distinct color transition induced upon external stimuli have made them a possible choice for colorimetric sensing applications. Because the chromogenic PDAs for TeDA, TrDA, and DiDA can be readily prepared by UV irradiation, subsequently, the colorimetric response toward heat and the organic solvent was investigated. We first began studying thermochromism of polymeric PDAs in the solid phase by heating gradually from 30 to 220 °C on a hot plate, which led to a naked-eye detectable periodic color change as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, PDAs absorb in the visible region and typically exhibit a blue color. Very importantly, the PDAs generate an assembly-related colorimetric responsetypically blue to redtoward external stimuli, and this unique property of PDAs has been extensively applied for various sensing applications. On the other hand, PDA offers intriguing morphological characteristics depending on molecular design and self-assembling behavior. In particular, these morphologies include films/sheets, , vesicles, nanowires/nanofibers, tubes, , crystals, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the color transition accepted by the research community is the structural transition of PDA's carbonic chain from planar to non-planar form when the compound is exposed to an external stimulus, and this transition is influenced by the lateral chain [39,40]. Chen et al (2012) [41] observed that the color transitioning of vesicles produced only with tricosadinoic acid occurred after NaOH addition. The color changes occurred due to the deprotonation of the carboxylic acids, from the polymer polar groups, which increased Coulombic repulsive force, leading to a new zig-zag PDA's polymeric carbonic chain [41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al (2012) [41] observed that the color transitioning of vesicles produced only with tricosadinoic acid occurred after NaOH addition. The color changes occurred due to the deprotonation of the carboxylic acids, from the polymer polar groups, which increased Coulombic repulsive force, leading to a new zig-zag PDA's polymeric carbonic chain [41][42][43]. Same behavior was observed for PDA films exposed to high pH conditions; however, steric impediment due to polymer matrix hampered the deprotonation of PDA carboxylic groups reducing the intensity of the color changes.…”
Section: Resultsmentioning
confidence: 99%
“…96 Red fluorescence intensity of 10,12-octadecadiynoic acid (C18)-coated sensors were approximately 20 times greater than that of TCDA (C23)-coated sensors. 96 These studies indicate that the composition of spacer, linker, and alkyl chain moieties have significant effects on detection sensitivity, however, more investigation is needed in this area. Kim and colleagues have further explored an alternative to DA−NHS intermediates by investigating DA−epoxy conjugates due to the known stability of epoxy groups under proper storage and their ability to readily react with amine groups.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 97%